CO₂ responsiveness of different plant functional types - Aston, Tim (Department of Biological Sciences, 2017)
Atmospheric CO₂ levels have increased by 30 % since the onset of the industrial revolution and are likely to continue to rise in the future. Whilst growth of plants is typically enhanced under elevated CO₂ concentrations, the degree of the response varies from species. In this study 4 species were exposed to 6 different CO₂ levels across a range from sub ambient to super ambient conceliltrations.